Argentina's Radical Party and popular mobilization, 1916-1930 - Horowitz, Joel, 1949- (Pennsylvania State University Press, 2008)
"Examines how Argentina's Radical Party rallied popular support in Buenos Aires from 1916 to 1930. Argues that the methods used for popular mobilization helped to undermine democracy. The popularity of President Hipólito Yrigoyen is explored, as well as the government's relationship with unions"--Provided by publisher.